Clinical and morphological evaluation of cutaneous ulcer cicatrization - a prospective study - Beatriz Guitton RB Oliveira; Juliana de O Araújo (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
The search aims to develop a clinical, histo-pathological and evolving evaluationof the cutaneous ulcer cicatrization in patients who have Peripherical Veiny Inefficience and/or Mellitus Diabets, trying to identificate factors envolved in the lateness of the repair process. It is a quantitative, prospective and descriptive study developed envolving patients from ambulatories having ulcer. The present search is enrolled in the Pro-Reitoria de Pesquisa e Pós-graduação da Universidade Federal Fluminense (Search and Post-Graduation Pro-Rectory of Fluminense Federal Unicersity) and has scholarship for Scientifical Beginning in the (CNPq - Conselho Nacional de Desenvolvimento Científico e Tecnológico) Scientifical and Technological Development National Council.